HUBUNGAN PEMBELAJARAN AQIDAH AKHLAK DENGAN PERILAKU SISWA KELAS IV DI MIS HARISUL KHAIRAAT OME KEC. TIDORE UTARA, KOTA TIDORE KEPULAUAN, MALUKU UTARA - Deviana Rahman, Vira; ihsan, Muzhir Ihsan; Rifatunisa, Adinda (JOURNAL EDUCATIONAL MANAGEMENT REVIEWS AND RESEARCH, 2024)
This research was motivated by students' poor behavior or attitudes, such as lying, not respecting parents or teachers, speaking bad words. Awareness of practicing lessons or understanding moral creed material in daily life is still lacking or not in accordance with religious teachings. This type of research uses correlational quantitative research techniques. The data collection methods used were questionnaires, observations and interviews. The data analysis technique used is Sparman's rank correlation. The results of the research obtained the highest and lowest scores for the moral aqidah lesson, namely the highest 72 and the lowest 44 with an average score of 59.81. Meanwhile, the highest score for student behavior was 73 and the lowest was 45 with an average of 65.25. The results of the linearity test obtained Fcount = 0.821 and Ftable = 04973, this data shows that Fcount > Ftable, this means that the linear model between learning moral beliefs and student behavior is very significant. After carrying out the hypothesis test, it was obtained that ???? = 0.734, after confirming the guideline table for providing an interpretation of the correlation coefficient, the value of 0.734 indicates that the correlation between learning moral beliefs and student behavior is strong. Based on the test above, it can be concluded that there is a strong relationship between learning moral beliefs and the behavior of class IV students at MIS Harisul Khairaat Ome for the 2022/2023 academic year.